PEMANFAATAN SUMBER BELAJAR DALAM IMPLEMENTASI KTSP - Suprayekti Suprayekti (Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2009)
Kurikulum Tingkat Satuan Pendidikan (KTSP) has been implemented nationally to meet the national standard of education. This school level based curriculum is to be developed on the basis of local needs and environmmental conditions without negelcting the content and competence standars decided at central level. Referring to the local needs and conditions, the implementation of KTSP curriculum can vary one school to the others. This article discusses how the schools utilize the available learning resources to support the implementation of KTSP curriculum. It is believed that the local learning resources could be integrated to KTSP curriculum as from planning, implementation and evaluation process of the instructions. Having discussed the possibilities of using local resources thorougly, the article offer some practical ideas how to do it.